2018
DOI: 10.2174/1874091x01812010036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucan and Vitamin D Supplementation on Obesity and Lipid Metabolism in Diabetic Retinopathy

Abstract: Background:Diabetes mellitus is a chronic disease manifested by an increase of blood glucose.Objective:To evaluate the effects of glucan and vitamin D supplementation in patients with diabetic retinopathy.Method:We evaluated the effects of 3-month supplementation with glucan and vitamin D in 54 patients with diabetic retinopathy. We measured levels of vitamin D, cholesterol, HDL cholesterol, and triglycerides.Results:The supplementation strongly decreased the cholesterol levels and improved the levels of HDL c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Lately, an association between vitamin D deficit and risk of DM2 development is being discussed in the literature (Lu et al, 2018). Our findings show that vitamin D supplementation helps to improve several clinical manifestation of DM2 and its complications (Zavorkova et al, 2018;Christiansen et al, 2010). Risk of DR development in overweight or obese individuals is well documented (Zhou et al, 2017) and further confirmed by our findings.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Lately, an association between vitamin D deficit and risk of DM2 development is being discussed in the literature (Lu et al, 2018). Our findings show that vitamin D supplementation helps to improve several clinical manifestation of DM2 and its complications (Zavorkova et al, 2018;Christiansen et al, 2010). Risk of DR development in overweight or obese individuals is well documented (Zhou et al, 2017) and further confirmed by our findings.…”
Section: Discussionsupporting
confidence: 84%
“…This study is a follow-up of previous observation showing effects of glucan on lipid metabolism and obesity in patients with DAR (Richter et al, 2018a;2018b;Zavorkova et al, 2018). In this study we report significant decrease of ORM levels after the end of the three-month treatment.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations